Non-invasive Treatment of Abdominal Aortic Aneurysm Clinical Trial (N-TA3CT): Design of a Phase IIb, placebo-controlled, double-blind, randomized clinical trial of doxycycline for the reduction of growth of small abdominal aortic aneurysm - Baxter, B. Timothy; Matsumura, Jon; Curci, John; McBride, Ruth; Blackwelder, William C.; Liu, Xinggang; Larson, LuAnn; Terrin, Michael L. (Contemporary clinical trials, 2016)
The Non-Invasive Treatment of Abdominal Aortic Aneurysm Clinical Trial (N-TA3CT) is a Phase IIb randomized, placebo-controlled clinical trial, testing doxycycline (100mg bid) for inhibition of growth in the greatest transverse, orthogonal diameter of small abdominal aortic aneurysms (AAA). We will enroll 258 patients, ≥55years of age who have AAA, men: 3.5–5.0cm and women: 3.5–4.5cm on CT scans confirmed centrally. The primary outcome is growth in maximal transverse, orthogonal diameter from baseline to 24-month follow-up. Secondary analyses address doxycycline effects on clinical events, aneurysm volume, and biomarkers. Primary analysis will be performed according to the principle of intention-to-treat accounting for death and ruptures by use of normal scores in analysis of covariance. At the time of the data file reported, 200 subjects have been randomized. We started enrollment in mid-2013 and will complete enrollment by mid-2016. Participant average age=70.9years, (SD=7.6years) and maximum transverse diameter=4.3cm for men (SD=0.4) and 4.0cm for women (SD=0.3). N-TA3CT is a critical experiment to determine whether doxycycline reduces growth of small AAA and systemic markers of inflammation previously seen in bench experiments and observational human studies to be associated with AAA growth. Our patient population baseline measurements agree with the design assumptions supporting our expectation of 90% power or greater to reject a null hypothesis in favor of an alternative hypothesis when growth is reduced by at least 40%. Registration: clinicaltrials.gov #NCT01756833.